(untitled) (American Journal of Pedagogical and Educational Research, 2025)
This study examines the ethical dimensions of artificial intelligence (AI) use in language learning. AI technologies hold transformative potential in educational processes, including personalized learning, accessibility, automated assessment, and learning analytics. However, these applications also present ethical challenges such as data privacy, algorithmic bias, access inequality, and academic integrity. The study explores the balance between the pedagogical advantages and ethical risks of AI in education, offering recommendations aligned with educational policies, AI literacy, equitable and inclusive system design, and academic integrity principles. Emphasis is placed on human-centered, transparent, and ethical AI use in education to enrich students’ learning experiences and support educational equity.